AI Judges and the Future Revolution of the Judicial Profession in Indonesia - Joice Soraya; Zico Junius Fernando (The Indonesian Journal of International Clinical Legal Education, 2024)
The implementation of AI in the criminal justice system can enhance efficiency, transparency, and fairness in legal decision-making by efficiently managing information and providing legal considerations based on objective data. In Indonesia, although the Supreme Court has initiated technology-based innovations such as e-Court and Smart Majelis and is considering the concept of AI Judges, technical, legal, and ethical challenges must still be carefully addressed. The application of AI must take into account the specific aspects of Indonesia's legal system, ensure algorithmic transparency, and protect human rights. This research employs a doctrinal (normative) legal approach, utilizing legal materials including primary, secondary, and tertiary sources. The approaches used are the conceptual approach, comparative approach, and futuristic approach. The nature of the research is descriptive-prescriptive, and the data analysis method employed is content analysis. The results of the research indicate that the application of AI in Indonesia’s judiciary has significant potential to improve efficiency and justice, but must be done cautiously and wisely. AI should be used as a supportive tool for human judges, rather than fully replacing them. The concept of AI Judges, where AI plays a role in legal decision-making, must be accompanied by regulations that ensure transparency, accountability, and the protection of human rights. With a careful and ethical approach, AI can be a significant innovation in the judicial system, helping to achieve faster, simpler, and more efficient justice in line with the fundamental legal principles of Indonesia and the values of Pancasila.